Athlete Experiences of Shame and Guilt: Initial Psychometric Properties of the Athletic Perceptions of Performance Scale Within Junior Elite Cricketers - Rice, Simon M.; Treeby, Matt S.; Olive, Lisa; Saw, Anna E.; Kountouris, Alex; Lloyd, Michael; Macleod, Greg; Orchard, John W.; Clarke, Peter; Gwyther, Kate; Purcell, Rosemary (Frontiers in Psychology, 2021)
Guilt and shame are self-conscious emotions with implications for mental health, social and occupational functioning, and the effectiveness of sports practice. To date, the assessment and role of athlete-specific guilt and shame has been under-researched. Reporting data from 174 junior elite cricketers (M = 17.34 years; females n = 85), the present study utilised exploratory factor analysis in validating the Athletic Perceptions of Performance Scale (APPS), assessing three distinct and statistically reliable factors: athletic shame-proneness, guilt-proneness, and no-concern. Conditional process analysis indicated that APPS shame-proneness mediated the relationship between general and athlete-specific distress (p < .01), with this pathway non-contingent on sex or past 12-month help-seeking for mental health concerns (p's > .05). While APPS domains of guilt-proneness and no-concern were not significant mediators, they exhibited correlations in the expected direction with indices of psychological distress and wellbeing. The APPS may assist coaches and support staff identify players who may benefit from targeted interventions to reduce the likelihood of experiencing shame-prone states.